A Clinical Study of Cauterization of Sphenopalatine Artery for Idiopathic Refractory Posterior Epistaxis - Tunjai Namiq Faiq; Ozdan Akram Ghareeb (Research Highlights in Disease and Health Research Vol. 1, 2023)
Refractory posterior epistaxis necessitates sphenopalatine artery cautery. The current study aimed to estimate the efficiency of cautery the sphenoid artery and to observe postoperative complications. This prospective clinical study of 200 consecutive adult patients with posterior epistaxis was conducted in a private specialized hospital and clinic in Kirkuk, northern Iraq, from the period from February 2019 to September 2021. The nasal cavity of each participant was carefully examined endoscopically to find out the location of the bleeding, and then determine the necessity of surgical intervention. A total of 200 epistaxis cases were included, with posterior epistaxis accounting for 12 (6%) of all epistaxis cases requiring sphenoid artery cauterization. According to the findings, the success rate of all surgical cases was 100%, as no serious complications were observed during or after endoscopic cauterization, with the exception of one case of numbness of the palate, which gradually disappeared during the first three months after the procedure. As a result, we concluded that cautery of the sphenopalatine artery produces better results and should be considered first-line treatment for idiopathic posterior epistaxis.